2006
DOI: 10.1586/14737159.6.3.399
|View full text |Cite
|
Sign up to set email alerts
|

Screening of HIV infection: role of molecular and immunological assays

Abstract: Due to technical improvements and new developments of immunological assays, the reliability of serological laboratory diagnosis of HIV infection has improved considerably and the residual risk, due to the diagnostic window for transfusion-transmitted HIV, has been reduced significantly. Through the addition of nucleic acid amplification tests (NAT) to blood donor screening, the residual risk can de further decreased by up to 50%, depending on the sensitivity of the NAT protocol and whether individual or pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 64 publications
0
34
0
4
Order By: Relevance
“…Currently, these new fourth-generation assays are widely used for routine laboratory diagnosis of HIV. Assay specificity is another important point to consider, and Weber determined the specificity of fourth-generation HIV assays launched after 2001 to be between 99.50% and 99.90% (6). Our study using the Architect HIV Combo assay showed comparable results (specificity, 99.78%; 95% CI, 99.75% to 99.80%).…”
mentioning
confidence: 58%
“…Currently, these new fourth-generation assays are widely used for routine laboratory diagnosis of HIV. Assay specificity is another important point to consider, and Weber determined the specificity of fourth-generation HIV assays launched after 2001 to be between 99.50% and 99.90% (6). Our study using the Architect HIV Combo assay showed comparable results (specificity, 99.78%; 95% CI, 99.75% to 99.80%).…”
mentioning
confidence: 58%
“…Over the last few decades, considerable efforts have been made to narrow the window period for detection of HIV (2). Although antibody (Ab) tests (third-generation assays) have been developed to reduce this period, they are not able to identify patients with acute HIV infection who have not yet produced specific antibodies.…”
mentioning
confidence: 99%
“…La técnica de ELISA utilizada en el tamizaje de VIH, ha experimentado numerosos cambios, ya que en el año 1985 se utilizaba lisado vírico como base antigénica, logrando detectar los anticuerpos 40 días después de la infección 45 . En el año 1987 el lisado fue sustituido por proteínas recombinantes y péptidos sintéticos, aumentando la sensibilidad y detectando la presencia de anticuerpos 33-35 días luego de la infección 46 . En el año 1994 la técnica ELISA adquirió el formato sandwich, logrando detectar anticuerpos IgG e IgM y reducir el período de detección a 22 días 46 .…”
Section: Artículo Originalunclassified
“…En el año 1987 el lisado fue sustituido por proteínas recombinantes y péptidos sintéticos, aumentando la sensibilidad y detectando la presencia de anticuerpos 33-35 días luego de la infección 46 . En el año 1994 la técnica ELISA adquirió el formato sandwich, logrando detectar anticuerpos IgG e IgM y reducir el período de detección a 22 días 46 . Actualmente, se utilizan técnicas que posibilitan la detección simultánea de anticuerpo y el antígeno p24, reduciendo el período de detección a aproximadamente 13-15 días, alcanzando un porcentaje de sensibilidad de 99,9% 45 .…”
Section: Artículo Originalunclassified